Outcomes and Complications of Ahmed Glaucoma Valve Implantation at Dr. Yap Eye Hospital - Widya A Reswari; Sri Wardhani; Krisna D P Jati; Erin Arsianti; Tatang Talka Gani; Retno Ekantini (Majalah Oftalmologi Indonesia, 2019)
Introduction and Objectives: Glaucoma drainage device is widely used in glaucoma surgery. Ahmed Glaucoma Valve (AGV) implant is one of the most used glaucoma drainages with a low incidence of complication. This study aimed to evaluate the outcomes and complication of Ahmed Glaucoma valve implantation in patients with refractory glaucoma at Dr Yap Eye Hospital Methods: Medical records of 30 patients (30 eyes) who had AGV implant surgery at Dr Yap Eye Hospital from January 2014 to October 2016 were reviewed. Pre-operative data include age, gender, eye laterality, type of glaucoma, visual acuity, and intraocular pressure and. The IOP, visual acuity (VA), and complications were measured at day 2, day 7, 1 month, 3 months, and 6 months. The postoperative complications were documented. Results: The mean IOP at baseline was 45.78 ± 13.04 mmHg, decreased after the operation to 14.41 ± 9.86 mmHg at day- 2 and 17.6 ± 14.6 mmHg at 6 months follow up. The mean initial VA was 2.47 ± 0.56 and unchanged 2.4 ± 0.74, at last, follow up. Early postoperative complications (0-3mos) were flat anterior chamber (4 eyes, 13%), hyphema (4 eyes, 13%), and tube exposure (4 eyes, 13%). The late postoperative complication (after 3 mos) was tube exposure (1 eye, 3%), bullous keratopathy (1 eye, 3.3%), and dislocation of the implant (1 eye, 3.3%). The rang of tube exposure onset was 49-235 days (mean 99.5 ± 90.54 days) after implantation. Flat anterior chamber and hyphema could be successfully managed conservatively while tube exposure needed surgical repair. Three cases of tube exposure required explantation. Endophthalmitis was detected in one case of tube exposure. Conclusion: AGV implantation appears to be a safe and effective surgical option in patients with refractory glaucoma.